Rethinking Ethics in International Affairs: Reshaping Civilizational Discourse - Zatari, Fadi K.S. (Journal of Al-Tamaddun, 2022)
The notion and applicability of ethics in the public sphere have become a relatively obscure matter with the prevailing incursion of political secularism. The functioning model of contemporary polity leads us to believe that ethics play no role in politics, whether at the national or international levels. Ethics is not a predominant concept in the leading international relations theories, such as realism and liberalism. Pacing these theories, for which the power struggle is a more central concept, this article argues that ethics play a significant role in politics and remains an essential element in understanding and analyzing foreign policy. Neglecting or ignoring ethics limits our appraisal and hinders us from perceiving the whole picture in analyzing international affairs. This article proposes a way forward through more responsible politics in dealing with and understanding global affairs. Responsible ethical politics means taking the best potentially ethical actions that circumstances permit at the national and international levels. This paper employs an interpretative approach with qualitative research via secondary published materials to engage the debate on ethics. In this study, the theoretical framework is the conception of al-Murūʼah (sense of honor), which presents a normative foundation for dealing with others nationally and internationally. Three sub-concepts develop from al-Murūʼah, First, al-Mu’āzarah (assistance without expecting compensation,) second, al-Miyāsrah (relieving others from discomfort or crises), and third, al-Ifḍāl generosity.